A CREATE-Based Educational Intervention to Improve Evidence-Based Practice Competencies in a Low-Income Country: A Feasibility Pilot Study - Ilaria Marcomini; Federica Buzzi; Andrea Poliani; Federico Chiodi Daelli; Fabio Ciceri; Jorge Carlos Naranjo Alcaide; Halima Ibrahim Malik Ali Omer; Debora Rosa; Giulia Villa; Rebecca Zanuso; Mohja Marhoom; Duilio F. Manara (Healthcare, 2026)
Background: Evidence-based practice (EBP) competencies remain limited in many low-income countries, where access to research training is often constrained by limited educational resources and humanitarian crises. This study evaluated the feasibility and preliminary effectiveness of a CREATE-based teaching strategy to improve EBP competencies among nurses and nursing students in Sudan. Methods: A quasi-experimental pre–post study without a control group was conducted among 29 participants (17 registered nurses and 12 nursing students) at Comboni College, Port Sudan. The intervention consisted of a 40 h synchronous online educational program based on the CREATE framework, integrating interactive lectures, practical group exercises, teach-back activities, and the collaborative development of an evidence-based Kangaroo Mother Care protocol. EBP competencies were assessed before and after the intervention using the EBP-COQ and EBP-COQ Prof© questionnaires. Paired-sample t-tests were used to compare pre- and post-intervention scores. Results: Nursing students demonstrated significant improvements in knowledge (p = 0.009), attitudes (p = 0.015), and overall EBP competency (p = 0.006), whereas changes in self-reported skills were not significant. Registered nurses showed significant improvements in knowledge (p < 0.001), skills (p < 0.001), and overall EBP competency (p < 0.001), while changes in attitudes and EBP utilization were not statistically significant. Conclusions: This pilot study suggests that a CREATE-based teaching strategy delivered through synchronous distance learning is feasible and may improve EBP competencies among nurses and nursing students in Sudan, despite the challenges of a resource-constrained and conflict-affected setting. Larger controlled studies are needed to confirm these findings and evaluate long-term educational and clinical outcomes.